EKSPERIMEN FISIKA MATERI FLUIDA STATIS DI SMAN 1 ANGKOLA TIMUR KELAS X BERBASIS SCIENTIFIC INQUIRY - Amalia Siregar, Yenni; Asmaidah Nasution, Seri (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
The aim of this research is to design a scientific inquiry model experiment on static fluid material which consists of 4 (four) phases, [1] presenting the problem to students, [2] students formulating the problem, [3] students identifying the problem in the investigation, [4] students find ways to overcome difficulties. Experiments carried out by students aim to improve students' investigative abilities.Â Where the results of the student's experimental assessment in experiment I correspond to phase [1] presenting the problem to students 71.87% [2] students formulating the problem 79.10 [3] students identifying the problem in the investigation 81.23% [4] students finding ways to overcome difficulties 84.33%. That aspects of students' investigative abilities based on the average score in each experiment have increased.Â